A Study of Governance Norms and Important Corporate Governance Practices in India’s Life Insurance Sector: Examining the Corporate Governance Practices in India's Life Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Indian life insurance sector has a pressing need for corporate governance. The development of life insurance businesses is impacted by corporate governance standards. And life insurance, in terms of corporate governance Insurance in India has a long history. Governance-models for corporations Regulatory instruments for corporate governance development corporate governance issues, Indian corporate governance Of the Study Which Discuses about Insurance , Life Insurance , Features of Life Insurance, Types of life insurance policies, History of Insurance in India, Corporate Governance, Need of Corporate Governance in Indian Life Insurance Industry, Corporate Governance in India, Current Indian Model of Corporate Governance